Slack, Shortage, and Discouraged Consumers in Eastern Europe: Estimates Based on Smoothing by Aggregation - Burkett, John P. (Review of Economic Studies, 1988)
As a consequence of aggregation over markets, the observed quantity may be less than the quantity demanded and less than the quantity supplied. To deal with such situations, a new technique is proposed for estimating demand and supply curves and the extent of shortage and slack. The technique is applied to the consumption goods markets of Czechoslovakia, the German Democratic Republic, Hungary, Poland, and Yugoslavia. It is found that shortage, even corrected for a discouraged consumer effect, is seldom as great as slack.